2018
DOI: 10.1002/ece3.3773
|View full text |Cite
|
Sign up to set email alerts
|

Correlated evolution between climate and suites of traits along a fast–slow continuum in the radiation ofProtea

Abstract: Evolutionary radiations are responsible for much of Earth's diversity, yet the causes of these radiations are often elusive. Determining the relative roles of adaptation and geographic isolation in diversification is vital to understanding the causes of any radiation, and whether a radiation may be labeled as “adaptive” or not. Across many groups of plants, trait–climate relationships suggest that traits are an important indicator of how plants adapt to different climates. In particular, analyses of plant func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 82 publications
2
19
0
Order By: Relevance
“…Since the site is in a fire‐dominated biome, the plants are also roughly the same age, adding another layer of standardization. Previous analyses using a single leaf per plant have detected significant trait‐environment associations in this group (Carlson et al., , ; Carlson and Holsinger, ; Prunier et al., ; Mitchell et al., , ). We measured traits commonly used in the literature and used in previous genus‐wide evolutionary analyses in Protea , i.e., leaf fresh water content (FWC), plant height (HEIGHT), leaf area (LA), leaf length‐to‐width ratio (LWR), leaf mass per area (LMA), and stomatal density (SD) (Table , Appendix S2).…”
Section: Methodsmentioning
confidence: 79%
See 2 more Smart Citations
“…Since the site is in a fire‐dominated biome, the plants are also roughly the same age, adding another layer of standardization. Previous analyses using a single leaf per plant have detected significant trait‐environment associations in this group (Carlson et al., , ; Carlson and Holsinger, ; Prunier et al., ; Mitchell et al., , ). We measured traits commonly used in the literature and used in previous genus‐wide evolutionary analyses in Protea , i.e., leaf fresh water content (FWC), plant height (HEIGHT), leaf area (LA), leaf length‐to‐width ratio (LWR), leaf mass per area (LMA), and stomatal density (SD) (Table , Appendix S2).…”
Section: Methodsmentioning
confidence: 79%
“…Previous work in Protea has found evidence for genus‐wide, clade level, and intraspecific trait‐environment associations with physiological and fitness consequences suggesting local adaptation (Carlson et al., ; Prunier et al., ; Heschel et al., ; Mitchell et al., , ). The traits linked to environmental gradients also have fitness consequences within wild populations (Carlson et al., ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although heat stress can be detrimental, in the CFR cold stress may impose a stronger selective pressure for growth (Wilson et al 2015). In fact, in a study of 56 Proteaceae species looking at climate and plant trait correlations, Mitchell et al, showed the most strongly supported evolutionary correlations to be between winter minimum temperature (next to mean annual temperature and elevation) and plant height (Mitchell et al 2018). They also note that this negative effect of elevation on plant height might be coupled potentially with shallower soils in the high elevation sites (Campbell & Werger 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Our study species, Protea repens (common sugar bush), is part of a lineage that has radiated over the past 5 to 18 million years to produce 112 species, ~85% of which are endemic (Rebelo 2001; Sauquet et al 2009). Along the environmental gradients Protea species inhabit, we have evidence for local adaptation and context-dependent benefits in several traits (Latimer et al 2009; Carlson et al 2011, 2016; Prunier et al 2012; Akman et al 2016; Mitchell et al 2018). There is also evidence for differential developmental plasticity and drought plasticity in leaf traits of several other Protea species ( Protea sect.…”
Section: Introductionmentioning
confidence: 99%